y = mx + b
y - b = mx
(y-b)/x = m
2006-10-23 10:23:07
·
answer #1
·
answered by Leah H 2
·
1⤊
0⤋
All u have to do is substitute the given values in the equation y = mx + b; u ll get the value of 'b' here (2, -1) --> (x,y) -1 = -9(2) + b -1 = -18 + b -1 + 18 = b b = 17 so equation is y = -9x + 17
2016-05-22 02:09:31
·
answer #2
·
answered by Ann 4
·
0⤊
0⤋
If there are no numbers to fill in you this is the way you'd do it!!!!
Y=MX+B
-B -B
_________
Y-B=MX
________
X X
The answer would be Y-B/X= M
You have to get the B on the side with the Y and then you would divide both sides by X which in return leaves B staniding alone the way you want it.........
2006-10-23 10:26:05
·
answer #3
·
answered by Chynadoll 2
·
1⤊
1⤋
re-arrange part by part:
y = mx + b
subtract b from both sides => y-b = mx
divide both sides by x => (y-b)/x = m
2006-10-23 10:36:58
·
answer #4
·
answered by Chris D 2
·
0⤊
0⤋
y = mx + b
y -b = mx +b -b
y - b = mx
y -b/x =m/x
y - b/x =m
2006-10-23 11:23:04
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
m stand for the slope which equal y*-y/(x*-x) ,and y* and x* any point
b stand for the point of interception with y-axis or x- axis
b = (0,y*) or (x*,0) so y* or x*=b
m=b-y/(0-x) => b-y/-x => y-b/x
or m=0-y/(b-x) => -y/(b-x) => y/(x-b)
2006-10-23 10:38:41
·
answer #6
·
answered by Khalidxp 3
·
0⤊
0⤋
Y=MX+B
-B=-B
Y-B=MX
/X=/X
(Y-B)/X=M
2006-10-23 10:24:07
·
answer #7
·
answered by makawao_kane 6
·
1⤊
0⤋
m=(y-b)/x
because:
y=mx+b
y-b=mx
(y-b)/x=m
2006-10-23 10:24:09
·
answer #8
·
answered by 1234abcd 2
·
1⤊
0⤋
y=mx+b
y/x=m+b/x
mx+b=y
mx=y-b
m=(y-b)/x
2006-10-23 10:24:28
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋
-mx=-y+b
mx=y-b
m=(y-b)/x
2006-10-23 10:24:21
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋